Effect of slip on MHD flow of fluid with heat and mass transfer through a plate - Ramzan M.; Shafique A.; Abbas S.; Ali E.; Alharthi A.M.; Jan R. (Taylor and Francis Ltd., 2025)
Fractional order derivatives are recognized as advanced mathematical tools with broad applications in physics and engineering for deriving real-world solutions. This study examines a fractional order model of a non-linear Casson fluid, highlighting the widespread utility of fractional derivatives. Additionally, the problem incorporates the Dufour and slip effects. Specifically, the constant proportional Caputo fractional model is formulated using generalized Fick's and Fourier's laws. Initially, the governing equations are transformed into a non-dimensional form and subsequently solved using the Laplace transform. Analysis of the figures indicates that the Casson parameter reduces fluid motion, while the diffusion thermo effect enhances it. Furthermore, the study includes a comparison between fractionalized and ordinary velocity fields. Highlight: Introduction of novel CPC fractional derivative model of Casson fluid flow. Semi-analytically solutions using Laplace transform method for accurate fluid behavior representation. comprehensive parametric analysis linking theoretical findings. Temperature contour affected by significant values of Du?. ? 2024 Informa UK Limited, trading as Taylor & Francis Group.